Retardation mechanism of anionic asphalt emulsion on the hydration of Portland cement. (28th February 2018) - Li, Wei; Hong, Jinxiang; Zhu, Xiaobin; Yang, Dingyi; Bai, Yun; Liu, Jiaping; Miao, Changwen
Highlights: Retardation effect of anionic asphalt emulsion on cement hydration was confirmed by setting time, hydration heat and electrical resistivity. The results of MIP and SEM validated that cement-asphalt paste is more porous in comparison to pure cement paste. ESEM was employed to observe the adsorption of asphalt membrane onto the surface of cement grains. Hydrogen bonds formed between different water molecules in anionic asphalt emulsion reduced the reactivity of water molecules with cement. Abstract: Cement-asphalt (CA) mortar, a grouting material consisting of Portland cement (PC), asphalt emulsion, sand, water and other related admixtures, has been widely used as a cushion layer material in the construction of High-Speed Railways (HSR) during the past decade in China due to its excellent damping property. The fresh and hardened properties of CA mortar are closely related to the PC hydration in the presence of asphalt emulsion. However, the retardation effect introduced by the anionic asphalt emulsion on the hydration process of PC has not been fully understood. In this paper, the effect of an anionic asphalt emulsion on the early hydration process of CA paste was first investigated by setting time test, isothermal conduction calorimeter and electrical resistivity. The MIP and SEM were then employed to characterize the microstructure evolution of the CA paste. Based on the data and observation obtained from the experimental study, three possible retardation mechanisms introduced by the anionic asphalt emulsion on the PC hydration were then assessed in this paper, including (i) selective adsorption by anionic emulsifier via electrostatic attraction, (ii) coating formed by the demulsification of anionic asphalt emulsion, and (iii) reduced reactivity of water molecules in anionic asphalt emulsion.